The Efforts of Attorney Offices to Resolve Criminal Cases Based on the Concept of Restorative Justice - Joko Sriwidodo (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
Recently, several cases show the criminal justice system in Indonesia has not guaranteed legal certainty and justice for the people. Thus, it is necessary to have a breakthrough in Indonesia’s criminal justice system by using the restorative justice approach. This approach is carried out by transferring and institutionalizing in accordance with justice. For this reason, it is necessary to have a specific regulation regarding the settlement of cases based on the concept of restorative justice in law enforcement institutions in Indonesia, especially in the attorney offices. The problems in this research are: How is law enforcement in Indonesia based on the concept of restorative justice? And how are the attorney’s efforts to resolve criminal cases based on the concept of restorative justice? This study aims to provide an overview of the restorative justice application. To respond to the senses of justice in society by implementing case resolution based on restorative justice. This normative legal research is conducted by library research through studying and analyzing primary, secondary, and tertiary legal materials. The research results show that the resolve of criminal cases by the Attorney General Office uses the Indonesian Attorney Office Regulation (PERJA) Number 15 of 2020 concerning Cessation of Prosecution Based on Restorative Justice.